PERANAN LEMBAGA TARI TRADISI DALAM MEMPERTAHANKAN TARI TRADISI - -, Y. Murdiyati (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
This article aims at analyzing the role of informal tradition dance organizations that preserve tradition dances and describing their strategies to maintain the preservation. The organizations that become the objects are "Irama Tjitra Yogyakarta" in Yogyakarta, "Sekar Budaya Nusantara" in Jakarta, and "Tunas Budaya" in Gunungkidul, Yogyakarta Special Territory. The study shows that each organization has a different role and strategies to do the preservation, among which are regeneration, transformation, transmission and revitalization. Key words: organization, tradition dance and role